The behavioural ecology of the Arctic fox (Alopex lagopus) in Iceland - Hersteinsson, P; Hersteinsson, Pall (1984)
﻿ During the last 20 years studies of various mammals and birds have shown that social organization is highly variable between and within species, and that such variation can frequently be explained on the basis of variation in food habits and food dispersion. This study is an attempt to discover the major ecological pressures affecting social organization and reproductive fitness of Arctic foxes in Iceland. Foxes were both studied at an individual level, by monitoring movements of radio-tagged foxes and observation of fox behaviour in demarcated study areas, and at the population level, by analysis of available foxhunting records, as well as material and information provided by foxhunters. The most common form of social organization was found to be a breeding pair, while social groups of 3-4 individuals also occur, particularly in coastal habitat, which is more productive and spatially more heterogenous with respect to food dispersion, than inland habitat. The Arctic foxes were found to occupy well defined, but fairly flexible group territories, whose borders were advertised by olfactory, auditory and visual signals. In one coastal region, three such territories ranged in size from 8.6 km2 to 18.5 km2, while there was an indication that territories were larger in inland habitats. In coastal habitats, foxes feed mainly on oceanic prey and do not show cycles in abundance. In inland habitat, foxes show a functional response to the 10 year population cycle of ptarmigan (Lagopus mutus), their main prey in winter. Litter sizes remain stable, however, due to little interannual variation in the foxes' summer diet, which consists mostly of migrant birds. Mean litter size at birth is 5-3 ± 1.7 S.D. and mortality from factors other than foxhunting is about 15% up to the age of weaning. Annual mortality in adults is about 50%, mostly due to foxhunting. Most vixens breed already as yearlings, while dog-foxes are more likely to show delayed breeding. In inland habitats there is balanced polymorphism with regard to colour morph, but in coastal habitats blue foxes have an overall selective advantage. Inland foxes are smaller than coastal foxes. Both size and colour affect reproductive fitness.